PENGARUH STRUKTUR KEPEMILIKAN TERHADAP MANAJEMEN LABA PADA PERBANKAN SYARIAH DI INDONESIA (Studi Kasus Pada Bank Umum Syariah di Indonesia Periode 2015-2019) - Deshinta Dwi Arumsari (Jurnal Ilmiah Penelitian Mahasiswa, 2022)
The purpose of this research is to determine the effect of ownership structure onearnings management in Indonesian Islamic banking. The variables tested in this studyconsisted of ownership concentration, institutional ownership, family ownership, stateownership, and earnings management. This study uses agency theory (agency theory)which explains the relationship between agent and principal. The data collection methoduses the documentation method. The analytical method used is descriptive statisticalanalysis, classical assumption test, multiple linear regression test, model accuracy test andhypothesis testing. Data analysis techniques in this study used Statistical Product andService Solutions (SPSS 26). The population in this study were all Islamic commercialbanks registered with the Financial Services Authority (OJK) during the 20152019 period.The sampling method was carried out by purposive sampling with a total of 11 Islamiccommercial banks used as the research sample.Keywords: Ownership Concentration, Institutional Ownership, FamilyOwnership, State Ownership, And Earnings Management.